Transcatheter mitral valve repair (TMVR) using MitraClip in patients younger than 65 years: a multicenter analysis of 2-years outcomes. (14th October 2021) - Mohammed, H; Plicht, B; Farah, A; Ohlow, M; El Garhy, M; Hesham, A; Ilse, J; Schols, W; Buck, T
Abstract: Background: TMVR using MitraClip became a well-established interventional therapy for severe MR. However, TMVR has been almost only applied to old aged patients rejected from surgical therapy. Objective: To present 2-years outcomes of 36 patients younger than 65 years with no surgical options treated by TMVR. Methods: A retrospective clinical and TEE study was conducted to evaluate 36 patients younger than 65 years treated by TMVR in 3 heart centers. Results: Mean age of the 36 study patients was 56.3±6.6 years, male gender was 72.2%. High operative risk was estimated by STS score (mean = 8.73±2.97) and EuroSCORE (mean = 24.71±12.79). All patients were refused for surgery by heart team decision, therefore admitted to TMVR. Baseline severity of MR was assessed by 3D-TEE based biplane vena contracta width (mean = 8.35±1.87 mm). Baseline transmitral mean pressure gradient was 1.81±0.78 mmHg. 21 patients showed mitral annular dilatation as the main cause of MR, 8 patients had leaflet prolapse, 4 patients exhibited papillary muscle displacement leading to leaflet tethering and 3 patients showed mitral leaflet thickening and/or retraction due to fibrosis. Procedural success was achieved in all patients with 1/2/3 clips implanted in 52.8%/44.4%/2.8% of cases with a mean of 1.5 clip per case. Two grades or more reduction in severity of MR (MR grade ≤ II/IV) was accomplished in 88.9% of patients. Mean postprocedural MPG was 3.78±1.96 mmHg. Average follow-up (FU) period was 25, 8 months and the median was 20 months (25th–75th percentile: 12–36 months). During 2-years FU, statistically significant difference (p value <0.002) was detected for NT-proBNP levels compared to baseline (mean = 9870±10819, median = 7748, 25th–75th percentile: 2702–14237 pg/ml) and at follow up visits (mean = 7645±11292, median = 3263, 25th-75th percentile: 883–8078 pg/ml). Furthermore, persistent symptomatic improvement during FU, defined as NYHA functional class improvement by 2 or more Grades, was achieved in 69% of patient in parallel with efficient reduction of MR in 34 patients so that a second intervention by reclipping was required in 2 patients to correct recurrent significant MR. Only two patients experienced procedure-related complications by large puncture site hematoma. No procedure-related mortality during the first 30 days was detected. However, mortality was recorded in 2 patients during the first month and was attributed to severe advanced heart failure in one case and septicemia after exclusion of infective endocarditis in another case. Over 2 years FU, other 5 patients passed away, 3 cases owing to advanced heart failure, one case due to multi-organ failure and one because of tumor disease. Conclusion: TMVR in patients younger than 65 years refused from surgical repair provides satisfactory clinical and echocardiography outcomes at 2 years. Future studies should evaluate the outcomes of MitraClip in this population in a larger cohort. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Hassan M.H. Mohammed received a scholarship grant from the Egyptian ministry of higher education and Minia University, Egypt.